ACTS OF TERROR COMMITTED BY THE ANTAGONIST IN NICHOLAS SPARKS’S SEE ME - Batmani Batmani; Shita Dewi Ratih P; Ni Made Widisanti S (Universitas Pakuan, 2020)
This study aims to analyze the antagonist in order to show the form of terror through acts of terror committed by the antagonist in Nicholas Sparks’ See Me. Processing data in this analysis uses descriptive-analytical methods and literature studies that are based on intrinsic and extrinsic elements as well as previous research on psychoanalytic terror. Based on the results of the analysis, the antagonist committed to acts of terror to Maria and this is expressed through every act of terror that he does. In addition, the antagonist does not have a mental disorder and this action is purely carried out on the basic of the hatred he holds, then turns into a desire to take revenge by committing acts of terror over his daughter’s death. The three acts of terror carried out by Avery were first, manipulating people, second, sending threatening message, and third by carrying out acts of violence which are part of the acts of terror.Keywords: antagonist; characterization; revenge; terror.